Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4314/ajtcam.v8i2.63204
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ethnoveterinary Remedies in the Management of Foot and Mouth Disease Lesions in a Diary Herd

Abstract: An outbreak of Foot and Mouth Disease (FMD) affecting 95 (57.2%) out of 166 cattle occurred in a medium-scale dairy farm in Kikuyu district, Kenya. Ethnoveterinary remedies of natural Soda ash solution (97% sodium bicarbonate), honey and finger millet flour were used to manage the FMD lesions. The lesions were washed with soda ash solution to remove the necrotic tissue after which raw honey and finger millet flour were applied to the cleaned lesions. The lesions were examined daily and those with necrotic mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…Literature on plants used in veterinary medicine, defined as ethnoveterinary medicine (McCorkle, 1986) and commonly referred to as Ethonoveterinary Practices (EVPs), is increasing, and is highly developed in some countries, for example Italy (Viegi et al, 2003). Recent papers for Africa (Gradé et al, 2009;Moreki et al, 2010;Opiro et al, 2010;Gakuya et al, 2011), America (Jernigan, 2009;Martinez and Lujan, 2011;Monteiro et al, 2011;Souto et al, 2011;Lans and Turner, 2011) and Asia (Gaur et al, 2010;Galav et al, 2010;Dilshad et al, 2010;Raziq et al, 2010;Phondani et al, 2010;Ghorbani et al, 2011;Deshmukh et al, 2011;Song and Kim, 2011) are testimony of this growing interest. Some recent works also discuss animals used in veterinary medicine, mainly in Brazil (Barboza et al, 2007;Confessor et al, 2009), and more information on zootherapeutic remedies can be found in Quave et al (2010) and Benítez (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Literature on plants used in veterinary medicine, defined as ethnoveterinary medicine (McCorkle, 1986) and commonly referred to as Ethonoveterinary Practices (EVPs), is increasing, and is highly developed in some countries, for example Italy (Viegi et al, 2003). Recent papers for Africa (Gradé et al, 2009;Moreki et al, 2010;Opiro et al, 2010;Gakuya et al, 2011), America (Jernigan, 2009;Martinez and Lujan, 2011;Monteiro et al, 2011;Souto et al, 2011;Lans and Turner, 2011) and Asia (Gaur et al, 2010;Galav et al, 2010;Dilshad et al, 2010;Raziq et al, 2010;Phondani et al, 2010;Ghorbani et al, 2011;Deshmukh et al, 2011;Song and Kim, 2011) are testimony of this growing interest. Some recent works also discuss animals used in veterinary medicine, mainly in Brazil (Barboza et al, 2007;Confessor et al, 2009), and more information on zootherapeutic remedies can be found in Quave et al (2010) and Benítez (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Honey has been used for the treatment of foot and mouth disease (FMD) lesions in dairy cattle in Kenya (15). Necrotic tissues were pre-cleansed with sodium bicarbonate solution 97% before daily application of raw honey or finger millet flour for three consecutive days.…”
Section: Cattle Sheep and Goatsmentioning
confidence: 99%
“…Feet of the affected animals may be washed with 2% copper sulphate solution. Washing of the wounds with soda ash solution and topical application of honey and finger millet is found suitable in foot lesions (Gakuya et al, 2011). Antiviral approaches including 2'-C-Methylcytidine (Meyer et al, 1997;Lefebvre et al, 2013), ribavirin ; cytokine therapy inclusive of IFN-α/β as an anti-FMD agent is useful for the purpose of prophylaxis in susceptible animals.…”
Section: Treatmentmentioning
confidence: 99%
“…1.18 2013a,b, 2014Deb et al, , 2013Madi et al, 2012;Teifke et al, 2012;Madhan Mohan et al, 2013;Xu et al, 2013). Recent developments in prophylaxis/vaccines and therapeutics also need to be utilized to their best potentials along with designing appropriate prevention and control measures for combating FMD and lessening economic losses being caused by this economically important disease of animals (Meeusen et al, 2007;Dhama et al, 2008Dhama et al, , 2013cDhama et al, , 2013dBae et al, 2009;Parida, 2009;Gakuya et al, 2011;Rodriguez and Gay, 2011;Dar et al, 2012a;Kim et al, 2012;Li et al, 2012a;Mahima et al, 2012b;Mohana et al, 2012;Pattnaik et al, 2012;Uddowla et al, 2012;Ayelet et al, 2013;Ding et al, 2013;Zheng et al, 2013;Tiwari et al, 2014).…”
Section: New Generation Vaccine Trials Against Fmdmentioning
confidence: 99%